Trap kitchen : wah gwaan Jamaican cookbook - Jenkins, Malachi; Smith, Roberto (Kingston Imperial, 2024)
Takes readers on a vibrant journey through Jamaica's rich culinary culture, offering over 60 recipes rooted in the island's history. The book features innovative twists on classic dishes such as Goat Head Soup, tender Oxtail, Ackee & Saltfish, and spicy Jerk Chicken. It promises a sensory adventure that explores the heart of Jamaican food traditions, blending history, culture, and unforgettable flavors.